The Effect of Shocks to Labour Market Flows on Unemployment and Participation Rates - Robert Dixon; Guay C. Lim; Jan C. van Ours (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper presents an analysis of labour market dynamics, in particular of flows in the labour market and how they interact and affect the evolution of unemployment rates and participation rates, the two main indicators of labour market performance. Our analysis has two special features. First, apart from the two labour market states - employment and unemployment - we consider a third state - out of the labour force. Second, we study net rather than gross flows, where net refers to the balance of flows between any two labour market states. Distinguishing a third state is important because the labour market flows to and from that state are quantitatively important. Focussing on net flows simplifies the complexity of interactions between the flows and allows us to perform a dynamic analysis in a structural vector-autoregression framework. We find that a shock to the net flow from unemployment to employment drive the unemployment rate and the participation rate in opposite directions while a shock to the net flow from not in the labour force to unemployment drives the rates in the same direction.
Keywords: E17; E24; J21; J64; 330; net labour market flows; unemployment rate; participation rate